2015
DOI: 10.1186/s40337-015-0048-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between body size attitudes and body image of 4-year-old boys and girls, and attitudes of their fathers and mothers

Abstract: BackgroundBody size attitudes and body image form early in life, and understanding the factors that may be related to the development of such attitudes is important to design effective body dissatisfaction and disordered eating prevention interventions. This study explored how fathers’ and mothers’ body size attitudes, body dissatisfaction, and dietary restraint are associated with the body size attitudes and body image of their 4-year-old sons and daughters.MethodsParticipants were 279 4-year-old children (46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
2
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 43 publications
3
74
2
10
Order By: Relevance
“…At these ages, some children want to be bigger and stronger in terms of their weight (Smolak, 2012), as they believe that the word strong is associated with overweight figures (Rich et al, 2008). As a result, they associate thinness with weakness (Cramer & Steinwert, 1998). Males reveal more of a desire to be physically bigger, which perhaps explains why boys are anxious to grow.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At these ages, some children want to be bigger and stronger in terms of their weight (Smolak, 2012), as they believe that the word strong is associated with overweight figures (Rich et al, 2008). As a result, they associate thinness with weakness (Cramer & Steinwert, 1998). Males reveal more of a desire to be physically bigger, which perhaps explains why boys are anxious to grow.…”
Section: Discussionmentioning
confidence: 99%
“…34, nº 1 (january) It was also found that most obese or overweight children do not perceive their weight status correctly (Burgess & Broome, 2012;Cramer & Steinwert, 1998;Tremblay et al, 2011). There are also errors, however, in the identification made by thin children (Cramer & Steinwert, 1998). In terms of gender, boys were more accurate than girls in estimating their body size (Holub, 2008) and, in general terms, children were better at perceiving height than width .…”
Section: Perception Of Body Sizementioning
confidence: 97%
See 2 more Smart Citations
“…Már a négyéves gyerekek tisztában vannak a megjelenésre vonatkozó társadalmilag elfogadott sztereotípiák-kal, megjelenik a vékony test preferenciája, a testi elége-detlenség és esetenként a tudatos fogyókúra is [12]. Ötéves lányoknál megfigyelhető a negatív testkép, az elhízástól való félelem, sőt sok esetben súlycsökkentő viselkedésformák is társulnak mindezekhez [13].…”
unclassified